2010
DOI: 10.1242/dev.048751
|View full text |Cite
|
Sign up to set email alerts
|

Opposite roles ofDMRT1and its W-linked paralogue,DM-W, in sexual dimorphism ofXenopus laevis: implications of a ZZ/ZW-type sex-determining system

Abstract: SUMMARYA Y-linked gene, DMY/dmrt1bY, in teleost fish medka and a Z-linked gene, DMRT1, in chicken are both required for male sex determination. We recently isolated a W-linked gene, DM-W, as a paralogue of DMRT1 in Xenopus laevis, which has a ZZ/ZW-type sex-determining system. The DNA-binding domain of DM-W shows high sequence identity with that of DMRT1, but DM-W has no significant sequence similarity with the transactivation domain of DMRT1. Here, we first show colocalization of DM-W and DMRT1 in the somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 23 publications
5
126
0
2
Order By: Relevance
“…This still unknown gene could antagonistically interact with DMRT1, for example, through changes of methylation patterns [1]. In amphibians with a ZW sex determination system, DM-W, a recently identified truncated paralogue of DMRT1 on the W chromosome, interacts antagonistically with DMRT1 and is known to trigger femaleness [19]. DM-W has no known homologue in chickens, although the current lack of sequence information for the W chromosome from other birds does not rule out the presence of a DMRT1 paralogue or other potentially female-determining genes in other avian lineages.…”
Section: Discussionmentioning
confidence: 99%
“…This still unknown gene could antagonistically interact with DMRT1, for example, through changes of methylation patterns [1]. In amphibians with a ZW sex determination system, DM-W, a recently identified truncated paralogue of DMRT1 on the W chromosome, interacts antagonistically with DMRT1 and is known to trigger femaleness [19]. DM-W has no known homologue in chickens, although the current lack of sequence information for the W chromosome from other birds does not rule out the presence of a DMRT1 paralogue or other potentially female-determining genes in other avian lineages.…”
Section: Discussionmentioning
confidence: 99%
“…The former is thought to determine sex in birds (Smith et al, 2009), whereas paralogs play this role in species of fish and frogs (Matsuda et al, 2002;Nanda et al, 2002;Yoshimoto et al, 2010). The antiMullerian hormone Amh likely determines sex in platypus (Cortez et al, 2014), whereas a paralog has been shown to play this role in a fish (Hattori et al, 2012).…”
Section: Lindragenmentioning
confidence: 99%
“…Mammals with DMRT1 loss-of-function mutations have impaired testicular development (Raymond et al 2000;Õunap et al 2004). In lower vertebrates, a duplicated and diverged copy of DMRT1, called DMY/DMRT1bY, is the male determinant in the Medaka Fish (Oryzias latipes) (Matsuda et al 2002;Nanda et al 2002), whereas a truncated copy, called DMW, antagonises DMRT1 function and participates in ovarian determinant in the African Clawed Frog (Xenopus laevis) (Yoshimoto et al 2008(Yoshimoto et al , 2010. Hence, this gene and its homologues clearly have a central role in vertebrate gonadal development.…”
Section: The Dmrt1 Gene and Testis Developmentmentioning
confidence: 99%